Intrahepatic Expression of Fatty Acid Translocase CD36 Is Increased in Obstructive Sleep Apnea - Rey, Esther; del Pozo-Maroto, Elvira; Marañón, Patricia; Beeler, Brittany; García-García, Yaiza; Landete, Pedro; Isaza, Stephania C.; Farré, Ramón; García-Monzón, Carmelo; Almendros, Isaac; González-Rodríguez, Águeda (Frontiers in Medicine, 2020)
Nocturnal intermittent hypoxia (IH) featuring obstructive sleep apnea (OSA) dysregulates hepatic lipid metabolism and might contribute to the development of non-alcoholic fatty liver disease (NAFLD) observed in OSA patients. However, further research is required to better understanding the molecular mechanisms underlying IH-induced hepatic lipid accumulation. Therefore, the aim of the present study was to determine the effects of OSA on hepatic CD36 expression and the impact of IH by using a mouse model of OSA. Histological analysis, lipid content and CD36 expression were assessed in livers from subjects who underwent liver biopsy and polygraphic study during sleep, and in livers from mice submitted to chronic IH mimicking OSA. Among those who presented OSA features, NAFLD were significantly more frequent than in control subjects with normal respiratory function (77.8% vs 36.4%, respectively), and showed more severe liver disease. Interestingly, CD36 expression was significantly overexpressed within the liver of OSA patients with respect to controls, and a significant positive correlation was observed between hepatic levels of CD36 and the values of two well-known respiratory parameters that characterized OSA: apnea/hypopnea index (AHI) and oxygen desaturation index (ODI). Moreover, hepatic lipid accumulation as well as induction of hepatic lipogenic genes, and CD36 mRNA and protein expression were significantly higher in livers from mice exposed to IH conditions for 8 weeks than in their corresponding littermates. This study provides novel evidence that IH featuring OSA could contribute to NAFLD setup partly by upregulating hepatic CD36 expression.